2005
DOI: 10.7326/0003-4819-143-4-200508160-00005
|View full text |Cite
|
Sign up to set email alerts
|

Warfarin plus Aspirin after Myocardial Infarction or the Acute Coronary Syndrome: Meta-Analysis with Estimates of Risk and Benefit

Abstract: For patients with the acute coronary syndrome who are at low or intermediate risk for bleeding, the cardiovascular benefits of warfarin outweigh the bleeding risks.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

3
149
1
13

Year Published

2006
2006
2018
2018

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 303 publications
(171 citation statements)
references
References 146 publications
3
149
1
13
Order By: Relevance
“…Meta-analyses of earlier studies with oral vitamin K antagonists combined with aspirin, as compared with aspirin alone, showed that there were reductions in recurrent ischemic events in patients after acute coronary syndromes. 4,5 In a large, observational analysis that included more than 40,000 patients with myocardial infarction, the use of triple therapy (aspirin, clopidogrel, and a vitamin K antagonist), as compared with aspirin alone, was associated with a rate of bleeding that was increased by a factor of 4, with no significant difference in the rate of survival. 29 Similar increases in bleeding events have been seen in other studies and other clinical settings in which the use of combined antiplatelet and anticoagulant therapy may be considered.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Meta-analyses of earlier studies with oral vitamin K antagonists combined with aspirin, as compared with aspirin alone, showed that there were reductions in recurrent ischemic events in patients after acute coronary syndromes. 4,5 In a large, observational analysis that included more than 40,000 patients with myocardial infarction, the use of triple therapy (aspirin, clopidogrel, and a vitamin K antagonist), as compared with aspirin alone, was associated with a rate of bleeding that was increased by a factor of 4, with no significant difference in the rate of survival. 29 Similar increases in bleeding events have been seen in other studies and other clinical settings in which the use of combined antiplatelet and anticoagulant therapy may be considered.…”
Section: Discussionmentioning
confidence: 99%
“…[1][2][3] Oral anticoagulation therapy with vitamin K antagonists reduces the incidence of recurrent ischemic events after myocardial infarction but also increases the risk of bleeding when it is added to aspirin or aspirin and clopidogrel. [4][5][6][7][8][9] Apixaban, an orally active, selective, direct factor Xa inhibitor, has been shown to reduce the incidence of venous thromboembolism in patients undergoing orthopedic surgery and to prevent thromboembolic events in patients with atrial fibrillation who are not candidates for oral vitamin K antagonist therapy. [10][11][12][13][14][15] We previously studied the use of apixaban, at doses of 5 to 20 mg daily, in patients who had had recent acute coronary syndromes and who were receiving aspirin or aspirin plus clopidogrel.…”
mentioning
confidence: 99%
“…It is still unproven, but it might be, that third-generation 'olimus'-eluting-stents require a shorter duration of TT. In a large clinical trial, in patients receiving new generation DES-zotarolimus [40,49,[52][53][54][55][56][57][58][59], no differences were observed between a 3-month DAPT vs. a 12-month DAPT. To answer at least some of the missing information, the MUSICA interventional trial [38] is currently enrolling more than 2,300 patients who will be assigned to receive TT or DAPT: the primary endpoint is the occurrence of ischemia, and the secondary endpoint consists of bleeding complications.…”
Section: Impact Of the Type Of Coronary Stents On Thrombotic Riskmentioning
confidence: 99%
“…Low-intensity oral anticoagulation (INR \ 2.0) in combination with aspirin did not reduce cardiovascular complications and increased bleeding compared to aspirin alone. The results of the meta-analysis guided by Rothberg et al bolsters the finding that after an acute coronary syndrome, VKAs plus aspirin decreases the rate of myocardial infarction or stroke more than aspirin alone [44]. Although the probability of major bleeding is also increased, the benefits would far outweigh the bleeding risks for many patients.…”
Section: Myocardial Infarctionmentioning
confidence: 99%